2019
DOI: 10.1024/1010-0652/a000238
|View full text |Cite
|
Sign up to set email alerts
|

The role of cognitive load in university students' comprehension of multiple documents

Abstract: Abstract. The study investigates the cognitive load of students working on tasks that require the comprehension of multiple documents (Multiple Document Comprehension, MDC). In a sample of 310 students, perceived task difficulty (PD) and mental effort (ME) were examined in terms of task characteristics, individual characteristics, and students' processing behavior. Moreover, it was investigated if PD and ME can still contribute to MDC while controlling for these variables. The perceived difficulty of the task … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Another factor that plays a role in comprehending documents is the readers' working memory. Research relating working memory and MDC is still in the early stages (e.g., Hahnel et al, 2019b), but shows that MDC is cognitive demanding for university students. Future research should further investigate the revealed commonality between STC and MDC by identifying the common source of variance.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…Another factor that plays a role in comprehending documents is the readers' working memory. Research relating working memory and MDC is still in the early stages (e.g., Hahnel et al, 2019b), but shows that MDC is cognitive demanding for university students. Future research should further investigate the revealed commonality between STC and MDC by identifying the common source of variance.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…Following previous research, we considered several variables to be indicators for standards of a documents model representation: time on texts (e.g., Hahnel et al, 2019 ), text switches as behavioral indicator of corroboration (e.g., Hahnel et al, 2019 ), corroboration in the essay (e.g., Rouet et al, 1996 ; Wineburg, 1991 ), source citation in the essay (e.g., Braasch et al, 2012 ), number of adversative connectors in the essay (List et al, 2021 ), and whether discrepancies were explicitly addressed in the essay (Stadtler et al, 2013 ). We articulated several predictions regarding readers' standards for constructing a documents model representation:…”
Section: The Present Studymentioning
confidence: 99%
“…In particular, the results on the influence of overload due to media use over the course of higher education studies stress the relevance of carefully filtering out and critically dealing with different kinds of information, which are considered crucial generic skills in the twenty-first century. As many current studies indicate, university students have great deficits when it comes to critically dealing with this multitude of media and online information (Hahnel et al 2019a;Hahnel et al 2019b;McGrew et al 2018;Zlatkin-Troitschanskaia et al 2019b). This is evidently the case for beginning students when entering higher education but also for advanced bachelor's and even master's students (Shavelson et al 2019;Nagel et al 2020).…”
Section: Discussionmentioning
confidence: 99%